2018
DOI: 10.1007/s10826-018-1247-5
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Physical Activity and Overweight: Does Caregiver Screen-Viewing Matter?

Abstract: Physical activity (PA) is essential for children's health and well-being, yet many children around the world do not meet the recommended PA levels. Screen-viewing behavior is one of the possible factors leading to low levels of PA and being overweight. Although research in Western countries shows that caregivers' screenviewing behavior and rule-setting are associated with their children's screen-viewing behavior, these results may not be generalizable to East Asian populations. Therefore, the current study pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 46 publications
0
25
1
Order By: Relevance
“…Standardized effects (including direct, indirect, and total effects) of the relationship between electronic health and shared decision making factors can eliminate the omitted-variable bias,36 the strength of including all the relevant factors in the same model is providing precise information on the contribution of each factor. Therefore, oncologists and other health care providers can compare the impacts among these factors using our models.…”
contrasting
confidence: 71%
See 1 more Smart Citation
“…Standardized effects (including direct, indirect, and total effects) of the relationship between electronic health and shared decision making factors can eliminate the omitted-variable bias,36 the strength of including all the relevant factors in the same model is providing precise information on the contribution of each factor. Therefore, oncologists and other health care providers can compare the impacts among these factors using our models.…”
contrasting
confidence: 71%
“…However, to the best of our knowledge, no studies have simultaneously considered all these factors in a model to investigate their impacts on patient communication. Given that simultaneously considering relevant factors can eliminate the omitted‐variable bias, the strength of including all the relevant factors in the same model is providing precise information on the contribution of each factor. Therefore, oncologists and other health care providers can compare the impacts among these factors using our models.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to these findings, Abonto et al 10 reported that the level of education of either parent was not related to OHRQoL. Because children learn and practice most of their parents' behaviour, 38 oral health behaviours of parents and thus that of their children can affect the children's OHRQoL. Dye et al 39 showed a direct relationship between mothers' and children's brushing habits.…”
Section: Discussionmentioning
confidence: 96%
“…Because children learn and practice most of their parents' behaviour, oral health behaviours of parents and thus that of their children can affect the children's OHRQoL. Dye et al showed a direct relationship between mothers' and children's brushing habits.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that regular and sufficient physical activity (PA) is associated with significant benefits for individual physical and mental health [1][2][3][4]. The World Health Organization formulated the widely acknowledged Health-Enhancing Physical Activity (HEPA) guidelines, suggesting that in order to receive these substantial health benefits, adults aged 18-64 years should accumulate at least 150 minutes of moderate-intensity PA per week, or 75 minutes of vigorous-intensity PA, or an equivalent combination [5,6].…”
Section: Introductionmentioning
confidence: 99%